2023
DOI: 10.1109/access.2023.3315595
|View full text |Cite
|
Sign up to set email alerts
|

Open Source Solutions for Vulnerability Assessment: A Comparative Analysis

Dinis Barroqueiro Cruz,
João Rafael Almeida,
José Luís Oliveira

Abstract: As software applications continue to become more complex and attractive to cyber-attackers, enhancing resilience against cyber threats becomes essential. Aiming to provide more robust solutions, different approaches were proposed for vulnerability detection in different stages of the application lifecycle. This article explores three main approaches to application security: Static Application Security Testing (SAST), Dynamic Application Security Testing (DAST), and Software Composition Analysis (SCA). The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…They find that although both open-source and commercial DAST tools can be effective, no single tool was effective in finding all the vulnerabilities. Cruz et al [28] compare Open-Source SAST, DAST, and Software Composition Analysis (SCA) tools. The authors found combinations of tools were more effective than using one particular tool or approach.…”
Section: Comparing Static Application Security Testing (Sast) and Dyn...mentioning
confidence: 99%
“…They find that although both open-source and commercial DAST tools can be effective, no single tool was effective in finding all the vulnerabilities. Cruz et al [28] compare Open-Source SAST, DAST, and Software Composition Analysis (SCA) tools. The authors found combinations of tools were more effective than using one particular tool or approach.…”
Section: Comparing Static Application Security Testing (Sast) and Dyn...mentioning
confidence: 99%